Isolation, Morphological Characterization, Biochemistry, and Antagonistic Activity of Endophytic Bacteria from Rice Against Xanthomonas oryzae pv. Oryzae - Saipul Sihotang; Alfons Dwi Putra Butar-Butar; Lita Nasution; Haliatur Rahma; Trizelia Trizelia; Magdalena Saragih; Retna Astuti Kuswardani; Ika Listiana; Beatrix Sofranes Napitupulu (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Endophytic bacteria have the potential as environmentally friendly biocontrol agents in controlling bacterial leaf blight (BLB) in rice caused by Xanthomonas oryzae pv. oryzae (Xoo). This study aims to isolate, characterize morphology and biochemical tests, and test the antagonistic activity of endophytic bacteria from rice against Xoo. Isolation was carried out from healthy rice root tissue using a surface sterilization method. Morphological characterization included colony shape, color, edge, elevation, and Gram properties, while biochemical characterization included catalase, oxidase, motility, starch hydrolysis, and sugar fermentation tests. The antagonistic test used a dual culture assay method on NA (nutrient agar) media. The isolation results obtained six endophytic bacterial isolates (BETP 01–06) identified as the genus Pseudomonas and Bacillus with varying colony morphological characters. Antimicrobial activity test showed two potential isolates, BETP 03 (Pseudomonas) and BETP 05 (Bacillus), with an average inhibitory diameter of 16.3 mm and 16.5 mm against Xoo, respectively. Biochemical characterization showed that BETP 03 was bacillus, Gram-negative, citrate-negative, motile, gelatin hydrolysis positive, starch hydrolysis positive, and catalase positive; while BETP 05 was bacillus, Gram-positive, citrate-positive, motile, gelatin hydrolysis negative, starch hydrolysis positive, and catalase positive. These results indicate that both isolates have high potential as biological biocontrol agents in controlling bacterial leaf blight disease in rice.